Pengaruh Kepemilikan Manajerial, Kompensasi Bonus Terhadap Manajemen Laba Saat Sebelum dan Sesudah Kebijakan “PSBB” Diberlakukan Pada Sektor Industri Transportasi dan Logistik - William Kwestianus; Alby Tandinata; Yulius Christiawan (Business Accounting Review, 2021)
Agency theory is the employment relationship between the agent and the principal. Differences ininterests cause agency problems where the decisions taken by the agent are not in line with the principal. Theprincipal tendency to make profit as an indicator of company performance is the main reason why earningsmanagement practices occur. The existence of the